The factors that influence the integrity of financial statement: Indonesia case - Sekar Mayangsari; Melisa Fitryana Santoso (New Applied Studies in Management, Economics & Accounting, 2025)
This study examines the effect of independent commissioners, audit quality, leverage, profitability, and firm size on the integrity of financial statements. The agency and signaling theory are a basis for developing hypotheses. This study uses a quantitative method. The data comes from audited financial reports from 2018-2022. The sample in this study is the non-cyclical consumer listed firms. The sampling technique used was purposive sampling. This study uses multiple linear regression analysis using the SPSS 25.0 program in data processing. There are one hundred and fifty-five firms. The results of this study indicate that the Independent Commissioner and profitability positively affect the integrity of financial reports, and leverage and firm size negatively impact integrated financial reports. Unfortunately, audit quality has no significant influence on the integrity of financial reports. To test the integrity of financial statements, this study is the first to document evidence suggesting that the stock market perceives value in the information presented in integrated reports, beyond what is furnished in financial reports.